Heavenly vegan dals & curries : exciting new dishes from an Indian girl's kitchen abroad - Yadav, Rakhee (Page Street Publishing, 2019)
Rakhee Yadav, born and raised in India, simplifies and reimagines the traditional plant-based recipes of her childhood to create incredible meals the whole family will love. Each recipe in Heavenly Vegan Dals & Curries is bursting with the robust authentic flavor of Indian cooking and packed with nutrient-rich ingredients to yield satisfying, healthy dinners that are easy to make. The layered flavors of dals and curries make them versatile foods perfectly suited to becoming delicious, inexpensive meals with minimal effort<U+2015>like sweet and savory Sweet Chili Coconut Pineapple Curry, Garam Masala Brussels Sprouts & Navy Beans Curry with Applesauce and Spicy Sweet Potato Curry with Zucchini Fries. These recipes are easily customized to your tastes as you can often substitute the vegetables in the recipes for the ones you have on hand. With this cookbook you<U+2019>ll be able to whip up wholesome vegan dinners that can come together in 30 minutes as well as slow food suppers fit for Sunday night. Whether you<U+2019>re vegan or just trying to spice up Meatless Monday, Heavenly Vegan Dals & Curries has something for everyone at the table.